Legal Protection For Trademark Owners - Kartika, Nana (Inspiring Law Journal, 2024)
According to Law Number 20 of 2016 concerning Trademarks and Geographical Indications, to obtain rights to a trademark, the trademark must be registered with the Directorate of Trademarks of the Ministry of Law and Human Rights of the Republic of Indonesia according to the constitutive system. Indonesia adopts a first to file system, namely where the first party to submit an application for trademark registration gets priority to first register the trademark rights, then will get exclusive rights to their trademark and receive legal protection. So this provision is different from the norm adopted in Law Number 28 of 2014 concerning Copyright which adopts the principle of first to use. Exclusive rights can be defined as the right to "provide protection guarantees to the owner of the trademark and is the sole owner who has the right to use and use and prohibit anyone from having and using it